Investigating the Link between Critical Thinking Skill and Argumentative Writing Skill: The Case of Islamic Senior High School - RIZA OKTARI PUTRI (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2018)
This study was aimed at describing the link between the second year students’ critical thinking skill and their argumentative writing skill at Islamic Senior High School in Palembang, South Sumatera, Indonesia. There were 60 students participated in this study. The data were obtained by using two instruments: Cornell Critical Thinking Test (CCTT) and argumentative writing test. Pearson Product Moment Correlation Coefficient and regression analysis were used to analyze the data. From the result, statistically significant positive link between students’ critical thinking skill and their argumentative writing skill was found with correlation coefficient .695, and the p-value was (.000) lower than significance value (.000 < .005). Since there was a significant link, regression analysis was used. As the result, critical thinking skill had 48.4% contribution to the students’ argumentative writing skill. In short, critical thinking skill had relationship with argumentative writing skill, and it gave 48.4 % constribution to the students’ argumentative writing skill.